Concentrations, sources and ecological–health risks of potentially toxic elements in finer road dust from a megacity in north China. (15th July 2022) - Zuo, Ling; Lu, Xinwei; Fan, Peng; Wang, Lingqing; Yu, Bo; Lei, Kai; Yang, Yufan; Chen, Yurong
Abstract: Finer road dust has attracted considerable attention due to its more serious environmental detriment and ecological–health risk than coarser road dust. In this study, the concentrations of nine potentially toxic elements (PTEs, i.e. As, Co, Cr, Cu, Hg, Mn, Ni, Pb, and Zn) were analyzed in finer road dust with particle size <63 μm (FRD) collected from Shijiazhuang, a typical megacity in north China. Based on this investigation, the contamination levels, ecological–health risks, and sources of PTEs in FRD were comprehensively analyzed and the main pollution factors and areas of the high risks were identified. The results revealed that the average contents of As, Co, Cu, Hg, Pb, and Zn were significantly greater than the local soil background values. As a whole, the PTEs analyzed in Shijiazhuang FRD exhibited different contamination levels, viz. Hg was moderate to strong contamination; Zn was moderate contamination; Co, Cu and Pb were no-contamination to moderate contamination; As was no–contamination and no–contamination to moderate contamination; Cr, Mn and Ni were uncontaminated. The comprehensive ecological risks of PTEs in most sites were very high. The health risks of PTEs to the local inhabitants fell within safety limits. The pollution source analysis of PTEs showed that As and Hg were primarily derived from coal–related industrial source, which accounted for 27.5% of the total PTEs contents. Cu, Co, Pb, and Zn were mainly associated with traffic sources, which accounted for 26.5%. Mn, Ni, and Cr were principally generated by natural source, which accounted for 46.0%. It is worth noting that the coal–related industrial discharges and traffic emissions are the focus of anthropogenic sources control, which should be concerned. Graphical abstract: Image 1 Highlights: Accumulation of Hg, As, Co, Cu, Pb, and Zn were found in finer road dust. Hg exhibited moderate to strong contamination and significantly ecological risk. The overall ecological risk of potentially toxic elements was high. The health risks of potentially toxic elements in finer road dust is acceptable. Coal–related industrial and traffic activities are main anthropogenic sources.